Construction of Genomic Library and Screening of Edwardsiella tarda Immunogenic Proteins for Their Protective Efficacy Against Edwardsiellosis - Bothammal, Palanisamy; Ganesh, Mohan; Vigneshwaran, Vellaisamy; Anbarasu, Kumarasamy; Ponmurugan, Karuppiah; Al-Dhabi, Naif Abdullah; Natarajaseenivasan, Kalimuthusamy (Frontiers in Immunology, 2021)
Edwardsiella tarda is a severe aquaculture pathogen that can infect many hosts including humans, animals, and fish. Timely diagnosis and treatment are crucial for the control of edwardsiellosis in the aqua industry. By using rabbit polyclonal antibody, an expression gene library of virulent Edwardsiella tarda strain ED-BDU 1 isolated in south India was constructed and screened. The identified immune expressive proteins were characterized, and the corresponding coding sequences were cloned, expressed, and the purified recombinant proteins were used as antigens. The identified immunoreactive proteins namely HflC, HflK and YhcI were studied for their immune protective potential by in vivo by challenge experiments. The protective efficacy of HflC, HflK, and YhcI showed that the clearance of Edwardsiella from the host with ̴ 60% survivability. Further, the immunoreactive proteins induces a strong immune response upon infection and elicit the significant production of IL-10, IFN-ɣ, Th1, and Th2 mediated mRNA expression and were therefore effective in vaccine production for edwardsiellosis.